Characteristics of HPV prevalence in Sichuan Province, China. Issue 3 (December 2015) - Chen, Zuyi; Wang, Qingming; Ding, Xianping; Li, Qiongyao; Zhong, Rong; Ren, Huaying
Abstract: Objective: To investigate the distribution of HPV subtypes and analyze variation in infection trends during a 6-year period in Sichuan Province, China. Methods: A cross-sectional observational study was conducted at a center in Chengdu between January 1, 2009, and December 31, 2014. Patients with at least one type of cervical disease confirmed by histology and cytology were eligible for inclusion. Cervical specimens were tested for the presence of high-risk and low-risk HPV subtypes by reverse membrane hybridization. Results: Among 10 682 participants, 3370 women (31.5%) were infected with HPV. The most frequently detected high-risk genotypes were HPV16 (n = 791; 27.1%), HPV58 (n = 476; 16.3%), HPV33 (n = 273; 9.4%), HPV52 (n = 244; 8.4%), and HPV18 (n = 201; 6.9%). The most frequently detected low-risk genotype was HPV6 (n = 703; 40.8%). The detection rates of HPV33 (from 7.9% to 10.2%) and HPV58 (from 14.0% to 16.7%) increased over the 6-year period, whereas those of HPV16 (from 32.3% to 24.9%) and HPV18 (from 10.0% to 6.2%) decreased. The prevalence of HPV infection was highest among women aged 21–25 years (χ 2 = 191.189; P < 0.001). Conclusion: HPV58 and HPV33 were the most prevalent subtypes in Sichuan. Changes in the prevalences of infection with different HPV subtypes have been identified.